IMPROVING THE SYSTEM OF INNOVATION ACCELERATION IN THE COUNTRY: METHODOLOGICAL ASPECT - Liudmila TODOROVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Acceleration of innovation activities is the basis of both economic growth and social development at the present stage of the economic process development. In order to stimulate innovation activities one needs to study the methodology of developing the country’s innovation rankings. A number of indicators and indices, published during certain periods, are used in the study that evaluates innovation activities. We believe that it is necessary to develop an approach, which can serve as an impulse to make decisions and rationally use available economic resources in order to motivate people for intellectual work, train scientific researchers and establish national innovation "laboratories". For the management of innovative activity an important role is played by the expansion of the circle and improving the quality of information, on the basis of which the corresponding solutions are accepted. It is necessary along with private indicators of innovation to use in the analysis and management some consolidated, integrated, synthetic and generalizing indicators. It should be noted that the development of various types of integrated indicators and their characteristics is an extremely difficult task.